Cardiovascular and Kidney Outcomes and Mortality With Long-Acting Injectable and Oral Glucagon-Like Peptide 1 Receptor Agonists in Individuals With Type 2 Diabetes: A Systematic Review and Meta-analysis of Randomized Trials - Lee, Matthew M.Y.; Sattar, Naveed; Pop-Busui, Rodica; Deanfield, John; Emerson, Scott S.; Inzucchi, Silvio E.; Mann, Johannes F.E.; Marx, Nikolaus; Mulvagh, Sharon L.; Poulter, Neil R.; Badve, Sunil V.; Pratley, Richard E.; et al. (Diabetes Care, 2025)
BACKGROUND: Glucagon-like peptide 1 receptor agonists (GLP-1RA) reduce the incidence of major adverse cardiovascular events (MACE) in type 2 diabetes (T2D), although whether benefits extend to both subcutaneous and oral formulations remains unclear. PURPOSE: In these meta-analyses, including new data from the Semaglutide cardiOvascular oUtcomes triaL (SOUL) (oral semaglutide) and Evaluate Renal Function with Semaglutide Once Weekly (FLOW) trial, we examined cardiovascular (CV) and kidney benefits and risks of long-acting (defined as having pharmacokinetics sufficient to provide 24-h activity) GLP-1RA in T2D. DATA SOURCES: A systematic review of PubMed was conducted (to 7 February 2025). STUDY SELECTION: Randomized placebo-controlled CV and kidney outcomes trials of GLP-1RA with ≥500 individuals with T2D were included. DATA EXTRACTION: A random-effects model was used to estimate hazard ratios (HRs) for MACE, its components, all-cause mortality, hospitalization for heart failure (HHF), a composite kidney outcome (kidney failure [kidney replacement therapy or persistent estimated glomerular filtration rate [eGFR] <15 mL/min/1.73 m2], sustained ≥50% eGFR decline or nearest equivalent, or kidney-related death), worsening kidney function, and safety outcomes. DATA SYNTHESIS: Across 10 trials (n = 71,351), long-acting GLP-1RA reduced incidence rate of MACE by 14% (HR 0.86 [95% CI 0.81, 0.90]; I2 = 27.6%), HHF by 14% (0.86 [0.79, 0.93]; I2 = 2.1%), and the composite kidney outcome by 17% (0.83 [0.75, 0.92]; I2 = 20.4%) and all-cause mortality by 12% (0.88 [0.82, 0.93]; I2 = 17.5%). A consistent 14% reduction was seen for all MACE components. There was no significant heterogeneity by GLP-1RA administration route (subcutaneous vs. oral). There were no increased risks of severe hypoglycemia, retinopathy, or pancreatic events. LIMITATIONS: Trial-level meta-analyses preclude detailed subgroup analyses and may introduce ecological bias. CONCLUSIONS: As a group, long-acting GLP-1RA, including both injectable and oral formulations, reduce incidence of MACE, HHF, and kidney events and all-cause mortality in T2D.
CRIS-Team Scopus Importer:2025-05-16